Pontocerebellar Hypoplasia Type 6: A Rare Disorder in Two Siblings - Khan, Husnea Ara; Parvin, Jobaida; Saha, Dipa; Hossain, Sharmin; Hossain, Mohammed Monir; Saha, Narayan Chandra (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Pontocerebellar hypoplasia type 6 (PCH-6) is a mitochondrial disease caused by mutations in the RARS2 gene. It is characterized by severe neurodevelopmental impairment, progressive microcephaly, seizure, cerebellar and pontine hypoplasia. We present a detailed description of two siblings with PCH-6. They had similar symptoms like developmental delay, seizure, and microcephaly. Neuroimaging abnormalities were found in both patient but finding typical for PCH-6 was only found in patient-1. Whole-exome sequencing confirmed that both siblings harbored the same compound heterozygous c.1A>G (p. Met1?) and c.574_575delinsTT (p. Glu192leu) variant in RARS2 gene. This case report highlights the clinical features, and diagnosis of PCH-6 in two siblings. A heightened index of suspicion for PCH-6 is merited in infants with developmental delay, intractable seizure, and microcephaly. J Bangladesh Coll Phys Surg 2025; 43: 93-97